Combining Amines and 3-(2-Pyridyl)-[1,2,3]Triazolo[1,5-a]pyridine: An Easy Access to New Functional Polynitrogenated Ligands - Chiassai, Leonardo; Ballesteros-Garrido, Rafael; Clares, Maria Paz; García-España, Enrique; Ballesteros, Rafael; Abarca, Belén (Synthesis, 2019)
Triazolopyridine-pyridine amine ligands are easily obtained by means of either thermal- or copper(II)-mediated reactions. Starting from a readily accessible iodo derivative of triazolopyridine-pyridine and different amines, this new family of compounds combines aromatic and aliphatic nitrogen atoms with promising coordinating properties. Furthermore, chemical derivatization of a new triazolopyridine-pyridine diamine compound, N1-[6-([1,2,3]triazolo[1,5-a]pyridin-3-yl)pyridin-2-yl]ethan-1,2-diamine, allows the preparation of several remote-pyridine-containing ligands.
Keywords: triazolopyridines; nitrogenated ligands; copper catalysis; heterocycles